2024
DOI: 10.1038/s41413-023-00309-1
|View full text |Cite
|
Sign up to set email alerts
|

Age-related secretion of grancalcin by macrophages induces skeletal stem/progenitor cell senescence during fracture healing

Nan-Yu Zou,
Ran Liu,
Mei Huang
et al.

Abstract: Skeletal stem/progenitor cell (SSPC) senescence is a major cause of decreased bone regenerative potential with aging, but the causes of SSPC senescence remain unclear. In this study, we revealed that macrophages in calluses secrete prosenescent factors, including grancalcin (GCA), during aging, which triggers SSPC senescence and impairs fracture healing. Local injection of human rGCA in young mice induced SSPC senescence and delayed fracture repair. Genetic deletion of Gca in monocytes/macrophages was sufficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
0
0
0
Order By: Relevance
“…The relationship between bile acids and aging has also been demonstrated. Studies have shown that when bile acid metabolism is disturbed after adverse changes in the structure of the gut microbiota there is a significant increase in the body’s inflammation levels and an increase in the incidence of aging-related diseases, including Alzheimer’s disease and cardiovascular disease ( 8 ), but the relationship between bile acids and bone aging diseases remains to be demonstrated.…”
Section: Mechanism Of Gut Microbiota Metabolites Affecting Bone Metab...mentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between bile acids and aging has also been demonstrated. Studies have shown that when bile acid metabolism is disturbed after adverse changes in the structure of the gut microbiota there is a significant increase in the body’s inflammation levels and an increase in the incidence of aging-related diseases, including Alzheimer’s disease and cardiovascular disease ( 8 ), but the relationship between bile acids and bone aging diseases remains to be demonstrated.…”
Section: Mechanism Of Gut Microbiota Metabolites Affecting Bone Metab...mentioning
confidence: 99%
“…It has been demonstrated that senescence of skeletal stem cells in mice leads to greater release of pro-inflammatory and pro-resorptive factors into the bone senescence microenvironment leading to bone senescence ( 7 ). Senescent macrophages have also been shown to influence bone senescence by promoting inflammation and the release of granular calprotectin (GCA) ( 8 ). Also, chronic inflammation accelerates the aging of immune cells, leading to weakened immune function and an inability to remove senescent cells and inflammatory factors, resulting in a vicious cycle of inflammation and aging.…”
Section: Introductionmentioning
confidence: 99%